TARIX FANI DARSLARINI TASHKIL ETISHDA ZAMONAVIY TEXNOLOGIYALARNING ROLI - Xolikova, R.E. (SCIENCE and SOCIETY, 2023)
This article talks about the role of modern technologies in the teaching of historical science. The development of a student’s personality when organizing classes using interactive methods should begin with each teacher creating a foundation for himself. A teacher using innovative pedagogical technologies should give new knowledge, form, develop, strengthen skills, repeat knowledge, apply it in practice, teach taking into account the peculiarities of the academic subject in each subject.